Preliminary study of intention to stay among the IT employees in Klang Valley, Malaysia / Lee-Ching Kuo, Lee-Chen Lim and Navas Naghavi - Lee-, Ching Kuo; Lee-, Chen Lim; Naghavi, Navas (UiTM Cawangan Johor, 2018)
The purpose of this preliminary study is to examine the effects of human resource management practices on intention to stay among the IT employees in Klang Valley, Malaysia. The IT segment is worthy of study due to its expected growth and the increase in multinational companies operating in Malaysia. Responses from 123 survey respondents revealed that human resource management practices (career development opportunity, work-life balance, and compensation) have significant positive relationships with intention to stay. Furthermore, career development opportunity is found to be the best predictor of intention to stay among the IT employees in this study. In addition to the contribution to the intention to stay literature, the implications of this study may provide human resource practitioners insight into the drivers of intention to stay that is related to human resource practices.